2019
DOI: 10.1063/1.5091576
|View full text |Cite
|
Sign up to set email alerts
|

Controlling rotational quenching rates in cold molecular collisions

Abstract: The relative orientation of colliding molecules plays a key role in determining the rates of chemical processes. Here we examine in detail a prototypical example: rotational quenching of HD in cold collisions with H 2 . We show that the rotational quenching rate from j = 2 → 0, in the v = 1 vibrational level, can be maximized by aligning the HD along the collision axis and can be minimized by aligning the HD at the so called magic angle. This follows from quite general helicity considerations and suggests that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…Previous studies of Croft et al 24,25 and Morita et al 26,27 have shown that collision-induced resonances are more sensitive to the relative orientation of the colliding partners. Therefore, we have first scanned collision energies for the various entrance channels mentioned above to survey for any resonances.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies of Croft et al 24,25 and Morita et al 26,27 have shown that collision-induced resonances are more sensitive to the relative orientation of the colliding partners. Therefore, we have first scanned collision energies for the various entrance channels mentioned above to survey for any resonances.…”
Section: Resultsmentioning
confidence: 93%
“…The methodology used herein is, in many aspects, very similar to that utilized in the previous works of Croft et al 24,25 and Morita et al 26,27 except that reactive channels are also taken into consideration as a collision-induced outcome. Thus, upon a H + D 2 (υ, j) reactive collision (or likewise D + HD), the probability of detecting a scattered HD(υ , j ) product (or D 2 ) by a detector placed at Ω = (θ, φ), at a given collision en-ergy E coll , is governed by the state-to-state scattering amplitude 33 f J nn (θ, E coll ), i.e.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A large number of theoretical studies have illustrated in great detail the importance of the relative alignment of the colliding pair on the dynamics of cold diatom-diatom scattering. [18][19][20][21][22][23][24][25][26] Unfortunately, the vast majority of experimental work thus far has not explored the effect of the spatial alignment of the collision partners on the scattering process, and so there is very little data available for comparison with theory. Defining the initial state with this level of precision is equivalent to setting the boundary conditions for experimentally solving the dynamical equations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is much interest in studying inelastic and reactive molecular collisions near 1 K as well as in the mK (cold) and µK (ultracold) regimes [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Quantum effects are amplified in these regimes and quantum control of molecular collisions using external electric and magnetic fields becomes feasible [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%